Kenaf (Hibiscus cannabinus) Microbial Retting by Locally Isolated Fungi - Dayang Syahreeny, Bt Abang Mustafa (Universiti Malaysia Sarawak (UNIMAS), 2014)
Kenaf (Hibiscus cannabinus) is a cheap and versatile fiber. Retting is the major problem in applying high grade kenaf fibers that separate kenaf bast and core fibers. Fungal isolates were screened for pectinase and ligninase production via qualitative and quantitative measurement and seven fungal isolates were found to be promising. The fungal were identified via morphological identification, molecular identification using ITS primers and phylogenetic tree by Neighbour Joining method, which leads to their identification as Basidiomycota sp. UMAS EN1, Hypocrea lixii UMAS PALM1, Ceratocystis paradoxa UMAS PG3, Aspergillus nomius UMAS MW16, Aspergillus nomius UMAS P3, Aspergillus nomius UMAS JA2 and Pestalotiopsis olivacea UMAS PUC1. Fungal isolates UMAS EN1, UMAS PALM1, UMAS PG3 and PP mixed culture of UMAS PALM1 and UMAS PG3 were further opted as inoculums for kenaf retting trial. Kenaf retting was found to be better using fungal plugs under static condition. The evaluation of kenaf retting efficiency was based on the removal rate of pectin and lignin, enzymatic profile during kenaf retting and study of kenaf surface via SEM. As a result, the highest removal rate of pectin and lignin in kenaf retting was 79.05 ± 0.4 % and 40.67 ± 2.6 %, respectively with pectinase recorded as the predominant enzyme with highest activity at 2.486 ± 0.14 U ml-1. Besides, SEM revealed the removal of non-cellulosic components and separation of the bast fibers. PP mixed culture was further utilized in kenaf retting optimization. Physical retting factors of initial pH, temperature, retting period and inoculation size were selected and optimized using central composite design (CCD). CCD indicated that the initial pH and retting period had significant effects on pectin removal rate. Temperature of 25oC, initial pH of 4.0, inoculation size of 4 plugs and retting time of 4 days were the optimized condition estimated by the reduced model which predict 95.20% pectin removal rate as compared to 79.05% pectin removal rate at standard condition. A validation run was xii performed and pectin removal rate obtained was recorded as 91.00% which is comparable to maximum removal rate as predicted by the reduced model.